Analysis of TCI Index Using Landsat8 TIRS Sensor Data of Vaijapur Region - Gaikwad, Sandeep V; Kale, KV; Dhumal, Rajesh K; Vibhute, Amol D (International Journal of Computer Sciences and Engineering, 2025)
Vaijapur tehsil has faced drought disaster for decades, because it comes in scanty rainfall region of Maharashtra state. The agricultural sector has faced high impact of drought, so that, the reduction in cropland and production take place. The satellite sensors are used to monitor an earth temperature from the space. The Landsat 8 Thermal Infrared Sensor (TIRS) provides temperature data of the earth surface with 16 days temporal resolution. The preprocessing of Landsat 8 images was performed using ATCOR tool. This research study investigates drought severity level in Vaijapur tehsil on the basis of the Temperature Condition Index (TCI). We have used Landsat 8 TIRS (Thermal Infrared) Sensor data, to extract the TCI of the year 2013-2014. We have collected rainfall and temperature data from Indian Meteorological Department (IMD) web portal.